ANALYSIS OF THE QUALITY OF ADMINISTRATIVE SERVICES IN SUPPORTING E-KTP POPULATION AT THE DEPARTEMENT OF POPULATION AND CIVIL REGISTRATION IN TEBING TINGGI: English - Auliana Yuharini Purba; Muhammad Husni Thamrin (Indonesian Journal of Social Sciences, Policy and Politics, 2025)
The phenomenon of identity card digitization is carried out to replace old paper-based identity cards (KTP) nto more modern ones that can be accessed electronically. Along with the implementation of e-KTP, the government is required to provide good administrative services to ensure that the process of registration, renewal, and data verification can run efficiently and safely, and minimize errors in data management. The quality of administrative services is very important in supporting population management, especially in the implementation of e-KTP. Public service is defined as the government provides fair, efficient, and transparent services to meet the needs of the community. Quality services will increase public satisfaction. The Population and Civil Registration Office (Disdukcapil) of Tebing Tinggi City is an office that has the task of exercising authority in the field of population administration management located in Tebing Tingg City. This research was conducted at the Population and Civil Registration Office (Disdukcapil) of Tebing Tinggi City. which aims to describe the quality of e-KTP administration services in Tebing Tinggi City. The results showed that the physical appearance dimension of office facilities and infrastructure was quite good. However, employee reliability still needs improvement because there is a gap between community expectations and reality in the field, which results in community dissatisfaction. The responsiveness of officers in responding to requests is quite good, in accordance with their duties and responsibilities. The guarantee of time and cost clarity is also good. The empathetic attitude of employees in serving the community was also rated positively.